Konten Video YouTube: Pengaruh dan Peminatannya Bagi Mahasiswa Ilmu Komunikasi di Kota Makassar - Muhammad Yusuf AR; Syarmila Syam (Al-MUNZIR, 2022)
The purpose of this study was to determine the effect of YouTube video content on the interest in watching television among Communication Studies students in Makassar City. This study uses a quantitative approach with descriptive statistics to test the hypothesis about whether there is a relationship between the variables being studied. In addition, researchers also use the uses and gratification theory, that the selection of media used by the audience to meet their needs is looking for something they want. Also using the theory of technological determination, that every event or action taken by humans is the result of the influence of technological developments. This study aims to find out what types of video content students are most interested in when accessing video content on YouTube. The results of this study, among others, found that the most popular types of YouTube content based on the highest order were music and film content, video tutorials, video blogs (vlogs), culinary videos, traveling videos, entertainment videos, news and politics, game reviews, horror videos, business videos, motivational videos, documentaries, Islamic information, and religious lectures, so that it has implications for television media managers and content creators to pay attention to the content of interest. Keywords: YouTube Content, Social Media, Television Programs, Communication Science.